PERSONAL BRANDING CONSTRUCTION ON GEN Z INSTAGRAM: DIFFERENCES IN SELF-PRESENTATION ON GEN Z'S FIRST AND SECOND ACCOUNTS - Ruslan, Salwa Azzahra; Wiryany, Detya; Tawaqal, Rizki Surya (Universitas Gunadarma, 2025)
This study examines the construction of personal branding on Instagram among Gen Z by comparing self-presentation on primary and secondary accounts. Using Erving Goffman's (1959) dramaturgy theory as the main framework, this study highlights how Gen Z conducts impression management through digital media, where Instagram functions as a